Affective Disclosure of Value: emotional experience, neo-sentimentalism and learning to value. (20th July 2020) - Vanello, Daniel
Abstract: The aim of this paper is to motivate and solve a puzzle regarding the intuition that just as in the absence of perceptual experience we lack an important kind of understanding of sensory properties like colour, in the absence of affective experience we lack an important kind of understanding of value. The puzzle consists in understanding how can a property pertaining to the experience of the subject i.e. the affective component of emotional experience, provide us with a distinctive epistemic access to, and therefore an understanding of, properties that are instantiated by objects distinct from the experience i.e. the evaluative property of the object of experience. I argue that solving the puzzle necessitates us to commit to a metaphysical view of value according to which affective experience and evaluative properties are related by explanatory circularity. The upshot of the paper is that affective experience provides us with the sort of understanding of value that motivates the generation of evaluative concepts.